2021
DOI: 10.1002/etc.5016
|View full text |Cite
|
Sign up to set email alerts
|

Monarch Butterfly (Danaus plexippus) Life‐Stage Risks from Foliar and Seed‐Treatment Insecticides

Abstract: Conservation of North America's eastern monarch butterfly (Danaus plexippus) population would require establishment of milkweed (Asclepias spp.) and nectar plants in the agricultural landscapes of the north central United States. A variety of seed-treatment and foliar insecticides are used to manage early-and late-season pests in these landscapes. Thus, there is a need to assess risks of these insecticides to monarch butterfly life stages to inform habitat conservation practices. Chronic and acute dietary toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 40 publications
0
47
2
Order By: Relevance
“…Using the same concentrations from Experiment 2, we conducted a small bioassay on bumblebees to confirm the toxicity of clothianidin and imidacloprid used in our monarch studies (Supplemental Materials). Based partly on findings by Krishnan et al [40,56], we predicted that monarchs would be more tolerant of neonicotinoids (e.g., the lethal dose would be higher) than previous studies indicated, such as Pecenka and Lundgren [41]. In terms of flight performance, we predicted that monarchs exposed to neonicotinoids as larvae would fly shorter distances and fly slower, perhaps because of impaired neurological functions.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…Using the same concentrations from Experiment 2, we conducted a small bioassay on bumblebees to confirm the toxicity of clothianidin and imidacloprid used in our monarch studies (Supplemental Materials). Based partly on findings by Krishnan et al [40,56], we predicted that monarchs would be more tolerant of neonicotinoids (e.g., the lethal dose would be higher) than previous studies indicated, such as Pecenka and Lundgren [41]. In terms of flight performance, we predicted that monarchs exposed to neonicotinoids as larvae would fly shorter distances and fly slower, perhaps because of impaired neurological functions.…”
Section: Introductionmentioning
confidence: 83%
“…Olaya-Arenas et al [39] found no effect of clothianidin on survival or developmental time below 54 ng/g leaf on A. syriaca. In leaf disc studies, Pecenka and Lundgren [41] found an LC50 of approximately 9.8 ng/g (converted in Krishnan et al [56]) for clothianidin on A. incarnata. Krishnan et al [40] found an acute LC50 of 9.4 ug/g for imidacloprid and 0.8 ug/g for clothianidin on A. curassavica, which was similar to Krischik et al's [42] finding of 6 ug/g imidacloprid on A. curassavica.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Olaya‐Arenas et al (2020) also did not detect any synergistic effects when monarch larvae were chronically exposed to milkweed leaves treated with a cocktail of insecticides, fungicides, and herbicides at mean and maximum concentrations reported in Indiana agricultural settings. To further explore insecticide‐use patterns on landscape‐scale adult production, we could also incorporate the acute toxicity of foliar applications to eggs, pupae, and second‐generation adults as well as chronic insecticide effects on larvae that survive exposure to spray‐drift residues (Krishnan et al, 2021). However, as noted previously, even when assuming 100% mortality of monarchs downwind of a treated field, landscape‐scale adult productivity is greater when habitat is established within and outside the 38.1‐m buffer zone (Scenario 3) than when new habitat is planted only outside the no‐plant zone (Scenario 4).…”
Section: Discussionmentioning
confidence: 99%